2016
DOI: 10.1111/sode.12199
|View full text |Cite
|
Sign up to set email alerts
|

School Bullying and Moral Reasoning Competence

Abstract: To examine whether high moral reasoning competence of adolescents is associated with low levels of bullying, and to understand whether moral disengagement mediates or moderates this relationship, 925 German children ranging from 11 to 17 years of age (M = 14.18, SD = 1.21) completed questionnaires on moral reasoning competence and moral disengagement in surveys at three different schools. The children were classified according to their bullying role, based on a peer‐nomination procedure. Multinomial logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
14
0
5
Order By: Relevance
“…In an initial analysis of this data, we observed that moral competence reduced the likelihood of probullying but failed to motivate defending behavior (von Grundherr et al, 2016). In an initial analysis of this data, we observed that moral competence reduced the likelihood of probullying but failed to motivate defending behavior (von Grundherr et al, 2016).…”
Section: Moral Competence As a Moderator Of Peer Influencementioning
confidence: 78%
See 3 more Smart Citations
“…In an initial analysis of this data, we observed that moral competence reduced the likelihood of probullying but failed to motivate defending behavior (von Grundherr et al, 2016). In an initial analysis of this data, we observed that moral competence reduced the likelihood of probullying but failed to motivate defending behavior (von Grundherr et al, 2016).…”
Section: Moral Competence As a Moderator Of Peer Influencementioning
confidence: 78%
“…***p < .001. on by von Grundherr et al (2016). (yes = 1, no = 0); High MC, high-competence group (N = 125); INDIV, has individual been assigned the focal role (bully or defender)?…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the individual moral competency and motivation of every single group member does not allow an accurate prediction of individual bullying roles, these can slow down the social dynamic, which leads to bullying, if they are prevalent and promoted within the group [21]. There are strong reciprocity effects between environment and individual dispositions: the bullying initiator carries a defined profile, namely preference for dominance and good control over internal sanctions.…”
Section: A Moral Psychological Perspective For Prevention/ Interventionmentioning
confidence: 99%